2012
DOI: 10.1016/j.jcmg.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Edema as Detected by Pre-Contrast T1 and T2 CMR Delineates Area at Risk Associated With Acute Myocardial Infarction

Abstract: Objectives To determine whether cardiac magnetic resonance (CMR) in vivo T1-mapping can measure myocardial area at risk (AAR) compared with microspheres or T2-mapping CMR. Background If T2-weighted CMR is abnormal in the AAR due to edema related to myocardial ischemia, then T1-weighted CMR should also be able to detect and accurately quantify AAR. Methods Dogs (n=9) underwent a 2 hour coronary occlusion followed by 4 hours of reperfusion. CMR of the left ventricle was performed for mapping of T1 and T2 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
216
4
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 297 publications
(246 citation statements)
references
References 24 publications
10
216
4
7
Order By: Relevance
“…In the current work we show similar findings in myocardial infarction patients; namely, the extent of oedema identified by our optimised ROC threshold method, one week post-MI, is significantly larger than that measured by T2W-SPAIR, except in MVO+ patients where the difference is not statistically significant. This builds on the preclinical findings of O h-Ici et al [29] and Ugander et al [23], who have already demonstrated that T1 mapping can identify the area-at-risk, and the region so measured shows excellent correlation with microspheres. In the context of human studies, our work provides an interesting counterpoint to the findings of Dall'Armellina et al [3] who noted that T1 mapping and T2W-SPAIR detected similar oedema volumes in STEMI patients 24 hours post-MI.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the current work we show similar findings in myocardial infarction patients; namely, the extent of oedema identified by our optimised ROC threshold method, one week post-MI, is significantly larger than that measured by T2W-SPAIR, except in MVO+ patients where the difference is not statistically significant. This builds on the preclinical findings of O h-Ici et al [29] and Ugander et al [23], who have already demonstrated that T1 mapping can identify the area-at-risk, and the region so measured shows excellent correlation with microspheres. In the context of human studies, our work provides an interesting counterpoint to the findings of Dall'Armellina et al [3] who noted that T1 mapping and T2W-SPAIR detected similar oedema volumes in STEMI patients 24 hours post-MI.…”
Section: Discussionsupporting
confidence: 52%
“…Several oedema imaging methods exist-single-photon emission computed tomography, [26] T2W CMR, [19] LGE endocardial surface area, [27] T1 mapping CMR, [3,4,23] and T2 mapping CMR[13, 23]-but this study represents the first application of T1 mapping with a quantitative ROC-threshold optimised to a STEMI population. The precedent for such an approach was set by Ferreira et al [28], in a recent study on myocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This MRI approach is known to identify cardiac edema formation, and in the acute setting, this is equivalent to the myocardial area at risk. 17 As shown in Figure 2F and in representative midventricular short-axis MRI slices ( Figure 2G), myocardial edema determined 1 day after I/R was not different between CD73-null and WT mice. Thereafter, however, cardiac edema continuously decreased to baseline values within 28 days in the WT animals, whereas the respective values in CD73 −/− mutants tended to further increase.…”
Section: Cytokine Measurementssupporting
confidence: 50%
“…35) Native T1 mapping was also helpful in determining the area at risk (AAR) and yielded similar quantitative results, agreeing well with microspheres. 36) In reperfusion injury, the values at areas of microvascular obstruction (MVO) have been found to be slightly higher than those of remote myocardium, but lower than the surrounding infarcted area (Figure 2). 32,33) These T1 changes may persist for two months after the onset of the infarction.…”
Section: Clinical Applications Of Native T1 Mappingmentioning
confidence: 95%